The mediating role of knowledge application in the relationship between knowledge management practices and firm innovation - Egena Ode; Rajenthyran Ayavoo (Journal of Innovation & Knowledge (JIK), 2020)
This study empirically examines the relationship between knowledge management practices and firm innovation in the context of service firms in developing countries. The research also examines the mediating role of knowledge application in the relationship between knowledge management practices and firm innovation. From the literature review, this research develops a conceptual model that hypothesises a positive and significant relationship between knowledge generation, knowledge storage, knowledge diffusion, knowledge application and firm innovation. This research elicited responses using a questionnaire from a sample of 293 service firms in Nigeria. A drop-off-pick-up (DOPU) technique was used to obtain the data. The data was analysed using Structural Equation Modeling (SEM). The findings show that knowledge management practices contribute to firm innovation, both directly and indirectly. The results show that knowledge generation, storage and application have significant and positive effect on firm innovation. The findings also show that knowledge application mediates the relationship between knowledge generation, diffusion, storage and firm innovation. The findings imply that knowledge management practices contribute to innovation as a hierarchy, with the link through knowledge application having the greatest impact on firm innovation.
Keywords: 650; Firm innovation; Knowledge diffusion; Knowledge generation; Knowledge management; Knowledge storage; Services